ASSESSMENT OF QUANTITATIVE POINT-OF-CARE G6PD ACTIVITY BY USING CARESTART BIOSENSOR IN MALARIA ENDEMIC ZONE OF TUY DUC DISTTRICT, DAK NONG PROVINCE (Vietnam Journal of Community Medicine, 2022)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzymopathy in thehuman population, especially those living in malaria endemic areas. Decreased G6PD enzymaticactivity is associated with 8-aminoquinolines-induced hemolysis leading to severe complication, andmalaria elimination challenge, especially in Plasmodium vivax malaria. This study was conducted tothe enzyme G6PD activity deficiency in population are living in malaria endemic zone in Tuy Ducdistrict, Dak Nong province. Method: In order to inform the safer use of 8-aminoquinolines, a crosssectional study which included 2,809 subjects was conducted using a quantitative CareStart™ G6PDbiosensor (AccessBio, USA). Results: The results showed that the normal value of G6PD activityis 9.03 IU/g Hb, the adjusted male median is 8.78 IU/g Hb, the 30% and 80% cut-off values were2.63 IU/g Hb and 7.02 IU/g Hb, respectively. The overall prevalence of G6PD deficiency of studypopulation was 2,31%, with the figures for male and female were 3.65% and 1.49%, respectively. Theprevalence of G6PD deficiency was significantly different among ethnic minority groups (p
Keywords: G6PD deficiency, Plasmodium vivax, CareStart™ G6PD biosensor.